Analisis Kesulitan Mahasiswa Institut Teknologi dan Sains Nahdlatul Ulama Pasuruan pada Mata Kuliah Biologi Umum Materi Sistem Pencernaan Manusia - Sisca Desi Prastyaningtias (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
Learning difficulty students at the Nahdlatul Ulama Institute of Technology and Science Pasuruan in first semester for academic on year 2018/2019 which are marked by midterm scores in general Biology courses for human digestive system meterial that is deficient. Learning Difficulty student can lead to their lack of achievement in this course. This research was conducted to find out the factors of learning difficulty both internal and external by the students and the expectation is to be able to provide further input as an effort to resolve the difficulty learning to improve their learning achievement. This research is a qualitative descriptive study that aims to determine the internal and external factors that induces difficulty student Learning in General Biology courses in human digestive system material. The study used a descriptive design, tests, questionnaires and interviews to receive data. The research subjects are 32 students are from Biology, Mathematics, Physics and Agricultural Product Technology major. Based on the results of the study for the internal factors that cause their difficulty for Learning are study habits and ability material comprehension are still lacking as much as 59.37%, while the external factors are the lack of learning support tools as much as 59.37% and the condition of the house environment and around it as much as 50%.